Unsteady aerodynamic characteristics on trains exposed to strong wind and rain environment. Issue 226 (July 2022) - Yu, Mengge; Liu, Jiali; Zhang, Qian; Dai, Zhiyuan
Abstract: Crosswind associated with rainfall is a common weather condition, which threatens the operational safety of trains. This paper focuses on an investigation of the effect of crosswind associated with rainfall on train aerodynamics. The methodologies for reproducing the turbulent wind speed and instantaneous rainfall intensity are first described, and the calculation method of unsteady aerodynamic forces of trains operating in a wind-rain environment is set up using the quasi-steady method and weighting function method. Then the CFD technology is used to obtain the aerodynamic load coefficients of a train exposed to a wind-rain environment, and the computational model is verified with the experimental results. Finally, the unsteady aerodynamic load time histories, as well as the corresponding statistical characteristics of the train are investigated. The results demonstrate that the aerodynamic load coefficient is a function of yaw angle, rainfall intensity and wind velocity relative to the train under wind-rain conditions. The aerodynamic loads approximately obey normal distribution both for the quasi-steady method and weighting function method. The mean values of aerodynamic loads obtained by the two methods are almost the same, whereas the standard deviations computed by the weighting function method are smaller than those computed by the quasi-steady method. The dimensionless standard deviations of aerodynamic loads increase with the rainfall intensity, and are approximately linearly related to the rainfall intensity. The wind velocity relative to the train also has an impact on the dimensionless standard deviations of aerodynamic loads, and the impact becomes more obvious when the rainfall intensity increases. The dimensionless standard deviations of the aerodynamic loads can be expressed as quadratic polynomial functions of yaw angle, rainfall intensity and wind velocity relative to the train. Highlights: The formula for computing the unsteady aerodynamic forces of a train under the combined wind and rain action is proposed. The statistical properties of unsteady aerodynamic loads of a train operating in wind-rain environment are investigated. The unsteady aerodynamic loads of a train in wind-rain condition fluctuate more violent than those in crosswind condition. The dimensional standard deviations of aerodynamic loads increase with rainfall intensity.